Seroprevalence of Cytomegalovirus Among Pregnant Women at Kawempe National Referral Hospital, Uganda: A Cross-sectional Study - Katungye, Richard V; Musooko, Moses; Sekikubo, Musa; Mutabazi, Tobius; Kyohere, Mary; Tusubira, Valerie; Sendagala, Juliet Nsimire; Peacock, Joseph; Le Doare, Kirsty; Nakimuli, Annettee (Oxford University Press, 2025)
Maternal primary cytomegalovirus (CMV) infection is associated with abortion and congenital anomalies. In Uganda, the burden of maternal CMV infection is not well studied. This study thus assessed the seroprevalence and factors associated with CMV infection among pregnant women at Kawempe National Referral Hospital in Kampala. This work forms a part of the PROGRESS study, an observational cohort study undertaken in Kampala, Uganda, between November 2018 and April 2021. We conducted a cross-sectional study between September 2020 and January 2021 among the 639 pregnant women admitted to the labor ward at a government hospital. Sociodemographic, medical, obstetric, and socioeconomic data were collected. Blood samples from study participants were drawn and analyzed for the presence of CMV immunoglobulin G (IgG) and IgM using enzyme-linked immunosorbent assay-based quantitative assays. Further analysis of all IgM-positive samples was conducted using CMV IgG avidity assays. All infants had a nasal polymerase chain reaction (PCR) on the first day of life to investigate CMV positivity. Logistic regression was performed to determine the factors associated with CMV infection. Seroprevalence of CMV IgG among the 637 women was universal (100%), and that of CMV (IgM) was 5.8% (37/637). CMV (IgM) was associated with being low socioeconomic status (odds ratio, 3.44; 95% CI, 1.05-11.32; = .04). Transmission risk was low, and no infant had a positive PCR for CMV at birth. Universally, by the time women in Kampala conceive, they will have been exposed to CMV. Women of lower socioeconomic status were more likely to have recent CMV infection than their more affluent counterparts, highlighting the need for screening guidelines in this setting.